Particle morphology and magnetic properties of Ba0.5Sr0.5Fe12O19 powder calcined conventionally and by microwave heating - Kanagesan, Samikannu; Hashim, Mansor; Jesurani, Sinnappan; Thirunavukarasu, Kalaivani; Ismail, Ismayadi; Shafie, Mohd Shamsul Ezzad (Elsevier, 2012)
Barium strontium hexaferrite (Ba0.5Sr0.5Fe12O19-BSF) has been prepared by sol–gel process involving use of d-Fructose as a fuel. The prepared precursor was calcined in two different calcinations techniques conventional and microwave furnace. X-ray powder diffraction studies confirmed the formation of single phase Ba0.5Sr0.5Fe12O19. HR-SEM results show the morphology of the particles is hexagonal structures in platelet form. The average particle size of conventionally calcined BSF powder is 100–250 nm and that of microwave calcined powder is 30–100 nm. The broad hysteresis loop reveals that powder is well crystallized and exhibits hard magnetic properties.